Academics’ Role in Psychosocial Support for Students with Visual Impairments: A Case Study of Cahaya Qur'an Islamic Boarding School and Special School in Bogor - ria ceriana; Hidayaturrahmah Hidayaturrahmah; Hastuti Hastuti; Masykur Masykur; Widya Sari; Farhan Ramdhani (Jurnal Pengabdian Pemersatu Bangsa, 2026)
program and iftar gathering at Pesantren Tuna Netra and SLB Cahaya Qur’an, Bogor Regency. The program was conducted through preparation, implementation, evaluation, and reporting stages. The preparation stage included a needs assessment, fundraising, and coordination with the boarding school management. The implementation stage involved the distribution of social assistance, interactive sessions, motivational activities, Qur’an reading, and communal iftar. The results indicated that social support provided by academics and university students improved the psychological comfort, self-confidence, and motivation of visually impaired students. Warm interactions and a sense of togetherness played an important role in creating a supportive and inclusive environment. Although there were limitations in time and available assistance, the activity had a positive impact on the students and strengthened social relationships among academics, students, and the boarding school community.